Elena vanishing : a memoir - Dunkle, Elena; Dunkle, Clare B. (Chronicle Books, 2015)
"Seventeen-year-old Elena is vanishing. Every day means renewed determination, so every day means fewer calories. This is the story of a girl whose armor against anxiety becomes artillery against herself as she battles on both sides of a lose-lose war in a struggle with anorexia"--Amazon.com.